Modified unipolar SPWM inverter for solar PV applications using MATLAB/Simulink model interfaced with dSPACE DS1104 - Ashok, Kumar L; Kumaravel, R (Circuit world, 2023)
Purpose The purpose of this paper is to check the Solar Photovoltaic (PV) inverter working condition with modified unipolar switching pulse. The gate pulse for the inverter switches is generated in MATLAB simulation and interfaced with hardware protype. Simulation results can be compared with hardware results. Design/methodology/approach A considerable amount of research has been done on different Pulse Width Modulation (PWM) techniques. Based on the findings, a modified Unipolar Sinusoidal PWM technique was created with one reference signal and two carrier signals+ (one for the positive half cycle and the other for the negative half cycle) and simulated in the MATLAB/Simulink platform. The prototype inverter module receives the simulated switching pulses via dSPACE DS1104 hardware software interfacing board. The hardware implementation has been done, and the hardware results compared with simulation results for various input voltage levels using resistive load. Findings This modified switching pulse has dead band and additional hardware setup is not required. 3-phase multi-level inverter output waveform has been achieved with six switches in this method and with low filter values, pure sine wave output can be obtained in simulation. By this method of switching pulse generation and testing, for every modification in switching pulse hardware gate driver is not required. Resulting time consumption and money investment are lower. Originality/value Modified Unipolar SPWM pulse generation technique is novel method for solar PV inverter. The switching pulse has been designed and tested in both MATLAB/Simulation and hardware prototype inverter. Hardware and software results are identical. This method of pulse generation and hardware implementation has not been done anywhere before.